Efficacy and safety of intramuscular and intravenous midazolam for acute agitation in emergency settings: a systematic review - Federico Bottaro; Guido Nosari; Isidora Tesic; Paolo Brambilla; Giuseppe Delvecchio (International Clinical Psychopharmacology, 2026)
Acute agitation often requires parenteral sedation in emergency care. Midazolam is widely used for its rapid onset, short duration of action, and availability for intramuscular and intravenous administration, but its efficacy and safety across emergency settings remain incompletely understood. Following Preferred Reporting Items for Systematic reviews and Meta-Analyses 2020 guidelines, we searched PubMed, Scopus, and Web of Science for original studies evaluating intramuscular or intravenous midazolam, as monotherapy or in combination regimens, for acute agitation in emergency department (ED), psychiatric emergency service (PES), and prehospital emergency medical service (EMS) settings. Twenty-three studies met the inclusion criteria. Intramuscular midazolam was generally associated with rapid early sedation in ED studies, although this advantage was sometimes offset by less sustained clinical effects and higher need for rescue or additional sedation. Intravenous midazolam monotherapy showed a greater need for active airway management in its main direct comparison with intravenous droperidol. Midazolam-droperidol combinations showed more consistent advantages for rapid early sedation in monitored ED settings. In PES and EMS, midazolam’s role was more dependent on clinical context, operational constraints and postsedation monitoring. Midazolam appears a useful rapid-onset option, but should not be considered a consistently superior standalone strategy. Future multicenter studies should better elucidate its safest and most effective use.